Comparison in relation to the incidence of congenital syphilis and gestational syphilis in the last 5 years in the state of Piauí (Research, Society and Development, 2021)
Syphilis is a chronic infectious disease with its higher prevalence since antiquity and although its etiological agent and also as treatment measures are forgotten, syphilis is still a major public health problem worldwide, especially in countries with limited associated resources. to low investments in primary health care. Given the above, this research aimed to estimate a comparison between congenital syphilis and gestational syphilis stroke. Epidemiological data about the disease were obtained from the SUS Department of Informatics (DATASUS). From the data obtained, it is observed that gestational syphilis continues to have a high incidence in northeastern Brazil, with its peak in 2018, among pregnant women, most are in the age group of 20 to 29 years old. For congenital syphilis in the state of Piauí, most cases reported are recent congenital syphilis (93%), detected mainly during prenatal care, which ends up contributing to low mortality rates during prenatal care, which presents itself as a strategy that contributes to low disease-related mortality rates in the state of Piauí. Finally, one can request that the adoption of new strategies that result in effective assistance to pregnant women during prenatal care can be requested, with a view to adequate monitoring and timely diagnosis for syphilis in this population group, since This consequence will result in reduced reduction of congenital syphilis through more effective control of gestational syphilis.